Evaluation Of Spirulina, Nannochloropsis, and Chlorella Micro-algae Growth in Palm Oil Mill Effluent (POME) Medium with Variation of Medium Types and Time Adding Nutrient - Muhamad Zaini Mahdi; Yasinta Nikita Titisari; H. Hadiyanto; Marcelinus Christwardana (BIORE Scientia Publisher, 2022)
POME is a kind of liquid waste produced by the crude palm oil industry. POME was not treated adequately, resulting in an issue for the environment owing to excessive levels of COD and BOD. Algae is a kind of bio-absorbent that may neutralize contaminants in liquid waste. Microalgae need carbon, nitrogen, and phosphorus-containing ingredients to flourish. These nutrients are necessary for photosynthetic carbon sources to be converted into biomass. POME includes a high concentration of C, N, and P; hence this research aims to investigate the potential of POME as a medium for the development of algae such as Spirulina, Nannochloropsis, and Chlorella. The experiment was carried out by varying the nutrients, water type, and time of nutrient feeding. Urea and sodium bicarbonate were the nutrition. Preparing the medium, culturing the microalgae, assessing biomass, counting the algae cells, and creating a calibration curve were the procedures in the experiment. The findings revealed that POME is the best medium for microalgae, that Spirulina grows better in POME than Chlorella and Nannochloropsis, and that providing nutrients every 2 days was better than introducing nutrients at the beginning and without adding nutrients.